2023
DOI: 10.1002/fsn3.3596
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Chinese herb polysaccharide (CHP), gut microbiota, and chronic diarrhea and impact of CHP on chronic diarrhea

Hong Xue,
Chun‐Feng Mei,
Feng‐Yun Wang
et al.

Abstract: Chronic diarrhea, including diarrhea‐predominant irritable bowel syndrome (IBS‐D), osmotic diarrhea, bile acid diarrhea, and antibiotic‐associated diarrhea, is a common problem which is highly associated with disorders of the gut microbiota composition such as small intestinal bacterial overgrowth (SIBO) and so on. A growing number of studies have supported the view that Chinese herbal formula alleviates the symptoms of diarrhea by modulating the fecal microbiota. Chinese herbal polysaccharides (CHPs) are natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 248 publications
0
2
0
Order By: Relevance
“…In recent years, studies have shown that the extracts of medicinal plant active ingredients, including Chinese herbal polysaccharides, have been playing a positive role in livestock production and disease prevention and treatment (12). Chinese herbal polysaccharide can play a variety of biological functions (36,37), such as antiinflammatory (38), anti-tumor (39), antioxidant, lowering blood sugar, lowering blood lipids (40), immune regulation (41), and regulating intestinal flora (42), etc. Chen et al found that the basal diet supplemented with 1,000 mg/kg Lonicera fulvotomentosa extract could significantly increase the final weight of weaned piglets and the diversity and richness of intestinal flora in the jejunum and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have shown that the extracts of medicinal plant active ingredients, including Chinese herbal polysaccharides, have been playing a positive role in livestock production and disease prevention and treatment (12). Chinese herbal polysaccharide can play a variety of biological functions (36,37), such as antiinflammatory (38), anti-tumor (39), antioxidant, lowering blood sugar, lowering blood lipids (40), immune regulation (41), and regulating intestinal flora (42), etc. Chen et al found that the basal diet supplemented with 1,000 mg/kg Lonicera fulvotomentosa extract could significantly increase the final weight of weaned piglets and the diversity and richness of intestinal flora in the jejunum and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive growth of small intestine bacteria refers to the presence of excessive numbers of bacteria in the small bowel, which can cause gastrointestinal symptoms (Pimentel et al., 2020 ). Its clinical symptoms include malnutrition, abdominal distension, diarrhea, and abdominal pain (Chen et al., 2020 ; Xue et al., 2023 ) found that a quadruple probiotic combination consisting of Bifidobacterium infantis , Lactobacillus acidophilus , Enterococcus faecalis , and Bacillus cereus had anti‐inflammatory effects and could help repair damage of the intestinal barrier.…”
Section: Introductionmentioning
confidence: 99%